A study of outcome of caesarean myomectomy in a tertiary care hospital - Kaul, Shiveta; Abrol, Shivani; Jabeen, Farhat; Ali, Asifa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Uterine leiomyoma (i.e. fibroid or myoma) are benign clonal tumours arising from the muscle cell of the uterus .Uterine myomas are the commonest tumour over the age of 30 years and seen in 2% pregnant women. The impact of uterine myomas on pregnancy depends on the size, number and location of myoma. Myomectomy is a surgery to remove one or more fibroids. Recently, it has been suggested that caesarean myomectomy is a safe surgical modality if is performed in carefully selected patients. The aim of the study was to assess the safety and feasibility of performing myomectomy during caesarean section. Methods: This prospective observational study was conducted in the Postgraduate Department of Gynaecology and Obstetrics for a period of one and a half year in Government Lalla Ded Hospital – an associated hospital of Government Medical College, Srinagar which is the sole tertiary care referral centre in the valley. Results: A total of 54 patients were taken for caesarean myomectomy. Majority of the patients were in the age group of 26-30years and were of para-1 or 2. Mean blood loss was ≤500 ml during surgery. Most common intraoperative complication was haemorrhage and post-operative complication was fever. Conclusions: From the present study, it is concluded that with the advent of better anaesthesia and availability of blood, caesarean myomectomy is no longer a dreaded job in the hands of an experienced surgeon and in a well-equipped tertiary institution.